Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

a) y=(x+4)7-7)
Convert factored form to standard form


Sagot :

Answer:

[tex]y - 7x = 21[/tex]

Step-by-step explanation:

Given

[tex]y = (x + 4)7 - 7[/tex]

Required

Convert to standard form

[tex]y = (x + 4)7 - 7[/tex]

Start by opening the bracket

[tex]y = x*7 + 4*7 - 7[/tex]

[tex]y = 7x + 4*7 - 7[/tex]

[tex]y = 7x + 28 - 7[/tex]

[tex]y = 7x + 21[/tex]

Subtract 7x from both sides

[tex]y - 7x = 7x - 7x + 21[/tex]

[tex]y - 7x = 21[/tex]

Hence:

The standard form is: [tex]y - 7x = 21[/tex]